Caracterização da ocorrência de fratura em idosos: estudo epidemiológico em um hospital público - Toneto, Michelle Aparecida dos Santos (2022)
Introduction: Aging is considered one of the most significant changes of the 21st century. One of the characteristics of the aging process is the marked decline in functional capacity. With this, the elderly population becomes susceptible to the risk of accidents and falls that can cause fractures, leading to hospitalization and consequent increase in morbidity and mortality. Methodology: This is a descriptive, cross-sectional, documentary study with a quantitative approach, in which a prospective analysis was carried out on cases admitted to a public hospital, in the state of Minas Gerais, of elderly people aged 60 years or over, underwent a surgical procedure for fracture correction in any segment of the body, from August to October 2021. Data were obtained in two ways: I) interview through a structured questionnaire adapted for the study and II) document analysis information contained in the electronic medical record. Results: The mean age was 71.1 ± 8.96 years, being predominantly male. The main causes of fracture were the fall followed by traffic accidents. The most common type of fracture was that of the lower limbs, with the femur fracture being the most significant. The mean length of hospital stay was 14.1 ± 9.63 days. The most incident postoperative complications were pain, bleeding and mental confusion. About 9.8% went to the ICU in the postoperative period and the clinical outcome of death was found in 3.9% of the population studied. When correlated with the number of complications, the variables that presented statistical significance were the outcome, the ASA classification and the postoperative period. When correlated with the type of fracture, there was a statistical correlation between the type of fracture and length of hospital stay (p>0.0001) and with the sector of destination (p=0.002). Conclusion: This study made it possible to know the main postoperative complications and clinical outcome of the elderly undergoing surgical treatment for fracture correction, in addition to allowing the health team to better understand the profile of the elderly and the importance of health education for the public in general on the prevention of falls, external causes and violence against the elderly. In addition, it will also support discussions about the best surgical planning with the objective of reducing delays in performing the surgery and reducing the length of hospital stay.